Servitudes and Options in The Indonesian Translation of Terman’s By Balloon to The Sahara - Yusuf Arimatea Neno; Harris Hermansyah Setiajid (Universitas Muhammadiyah Semarang, 2023)
In the realm of translation, balancing the preservation of meaning and style while adapting to the linguistic and cultural context of the target language is crucial. This study investigates the application of Vinay and Darbelnet's concepts of servitude and option, referred to as